2019
DOI: 10.7812/tpp/18-195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori Treatment on Unexplained Iron Deficiency Anemia

Abstract: Surgeons write 1.8% of all prescriptions and 9.8% of all opioid prescriptions. Of a total of 180 patients (median age 63 years), 127 did not receive opioids; 53 were prescribed opioids against protocol. The operating surgeon was the only variable independently correlated with protocol adherence. Ambulatory breast surgery patients tolerated a nonopioid pain regimen well. Surgeons' decisions, rather than patient characteristics, primarily drove the choice of pain management in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…However, in a recent retrospective study by Daniel et al [16], they found no evidence that H. pylori is involved in causing IDA. IDA is resolved in most subjects regardless of H pylori treatment status.…”
Section: Results Of Previous Studies Have Implicatedmentioning
confidence: 92%
“…However, in a recent retrospective study by Daniel et al [16], they found no evidence that H. pylori is involved in causing IDA. IDA is resolved in most subjects regardless of H pylori treatment status.…”
Section: Results Of Previous Studies Have Implicatedmentioning
confidence: 92%
“…Tseng et al 29 conduziram uma coorte com 508 indivíduos da Califórnia com ADF inexplicada. Não houve nenhuma diferença na melhoria dessa condição após o tratamento da infecção por H. pylori, quando acompanhada por até 2 anos em comparação com aqueles que não foram tratados.…”
Section: Resultsunclassified
“…Mwafy et al investigated 150 H pylori ‐positive patients (18‐50 years old) and 150 matched controls for several hematologic parameters, and they found significantly lower levels of iron in infected patients compared to uninfected (71.6 ± 24.8 vs 80.1 ± 20.7 μg/dL) and similar results were obtained for vitamin B12 levels (262.5 ± 100 vs 378.2 ± 160.6 pg/mL) . Nevertheless, Tseng et al, who followed up 508 patients with IDA, did not report any significant difference on hemoglobin levels between those treated or not treated for H pylori after a 2‐year observation but that could also be due to the presence of intestinal metaplasia . Similarly, John et al did not find an association between H pylori infection and IDA; ethnic dissimilarities as well as differences in diagnostic criteria may also possibly explain these discrepancies.…”
Section: Hematologic Diseasesmentioning
confidence: 93%